Tephra sedimentation and grainsize associated with pulsatory activity: the 2021 Tajogaite eruption of Cumbre Vieja (La Palma, Canary Islands, Spain) - Bonadonna, Costanza; Pistolesi, Marco; Dominguez, Lucia; Freret-Lorgeril, Valentin; Rossi, Eduardo; Fries, Allan; Biass, Sebastien; Voloschina, Marija; Lemus, Jonathan; Romero, Jorge E.; Zanon, Vittorio; Pastore, Camille; et al. (Frontiers in Earth Science, 2023)
The 2021 hybrid Tajogaite eruption of Cumbre Vieja (La Palma) was mainly effusive, with >70% of magma volume erupted as lava and simultaneous explosive activity of variable eruptive styles (e.g., Strombolian, violent Strombolian, lava fountaining, ash-poor gas puffing), depositing a widespread tephra blanket. Tephra dispersal and grainsize features indicate violent Strombolian dynamics when field-based classification schemes are used. However, statistical analysis of pulsatory activity shows how rapid gas segregation and high magma ascent rate modulated the gas flux at the different vents, resulting in short-time fluctuations amongst the different eruptive styles and unsteady tephra ground accumulation. Various sedimentation processes were observed, including particle aggregation (especially during rainy atmospheric conditions) and different sedimentation features (e.g., lapilli waves, ash fingers). Grainsize distributions of 154 analyzed samples are unimodal with Md increasing from -2.2 to 2.3  (4.6-0.2 mm) and sorting decreasing from 1.6 to 0.4 at distances from vents between 0.7 and 5.3 km. The weight fraction of particles <1 mm (F1) increases with distance from vents for all selected layers and units, while the content in fine ash (particles <63m; F2) is <6 wt.%, with no clear correlation with distance. Total grainsize distributions of selected layers, units and of the whole tephra blanket are also unimodal with Md values between -0.5 and 1.4  (1.4-0.4 mm). The analysis of the Tajogaite eruption dynamics highlights the challenges of risk and crisis management associated with long-lasting basaltic pulsatory hybrid eruptions.